A distinct isoform of lymphoid enhancer binding factor 1 (LEF1) epigenetically restricts EBV reactivation to maintain viral latency. - B J H Ward; Kanchanjunga Prasai; Danielle L Schaal; Jian Wang; Rona S Scott (PLoS Pathogens, 2023)
As a human tumor virus, EBV is present as a latent infection in its associated malignancies where genetic and epigenetic changes have been shown to impede cellular differentiation and viral reactivation. We reported previously that levels of the Wnt signaling effector, lymphoid enhancer binding factor 1 (LEF1) increased following EBV epithelial infection and an epigenetic reprogramming event was maintained even after loss of the viral genome. Elevated LEF1 levels are also observed in nasopharyngeal carcinoma and Burkitt lymphoma. To determine the role played by LEF1 in the EBV life cycle, we used in silico analysis of EBV type 1 and 2 genomes to identify over 20 Wnt-response elements, which suggests that LEF1 may bind directly to the EBV genome and regulate the viral life cycle. Using CUT&RUN-seq, LEF1 was shown to bind the latent EBV genome at various sites encoding viral lytic products that included the immediate early transactivator BZLF1 and viral primase BSLF1 genes. The LEF1 gene encodes various long and short protein isoforms. siRNA depletion of specific LEF1 isoforms revealed that the alternative-promoter derived isoform with an N-terminal truncation (ΔN LEF1) transcriptionally repressed lytic genes associated with LEF1 binding. In addition, forced expression of the ΔN LEF1 isoform antagonized EBV reactivation. As LEF1 repression requires histone deacetylase activity through either recruitment of or direct intrinsic histone deacetylase activity, siRNA depletion of LEF1 resulted in increased histone 3 lysine 9 and lysine 27 acetylation at LEF1 binding sites and across the EBV genome. Taken together, these results indicate a novel role for LEF1 in maintaining EBV latency and restriction viral reactivation via repressive chromatin remodeling of critical lytic cycle factors.